Asymmetric microtubule nucleation from Golgi stacks promotes opposite microtubule polarity in axons and dendrites. - Yagoubat, A.; Conduit, P.T. (Current Biology, 2025)
The neuronal microtubule cytoskeleton is highly polarized, with most microtubules growing away from the soma in axons (plus-end-out), but many microtubules growing toward the soma in dendrites (minus-end-out). This differential microtubule polarity allows directional trafficking of specific organelles, vesicles, and molecules into either axons or dendrites, but how it is established and maintained remains unclear. We showed previously that microtubules are nucleated asymmetrically from Golgi stacks within the soma of Drosophila neurons, with their plus ends growing preferentially toward and into axons and away from dendrites. Here, we show that this microtubule nucleation asymmetry correlates with a cis-to-trans orientation of specific Golgi stacks toward the axon and depends on microtubule-nucleating ?-tubulin ring complexes (?-TuRCs) at the cis-Golgi and the plus-end-stabilizing protein CLASP at the trans-Golgi. Depleting CLASP or reducing ?-TuRC localization to the Golgi by depleting the Golgin protein GMAP (Golgi microtubule-associated protein) perturbs asymmetric microtubule nucleation and growth within the soma and results in polarity changes in proximal axons and dendrites. We propose that the plus ends of microtubules nucleated by ?-TuRCs at the cis-Golgi are stabilized by CLASP at the trans-Golgi to promote the growth of microtubules along the cis-to-trans Golgi axis. This, coupled with oriented Golgi stacks, promotes microtubule growth toward and into axons and away from dendrites, helping promote plus-end-out microtubule polarity in axons and maintain minus-end-out microtubule polarity in dendrites.